2000
DOI: 10.1007/3-540-44418-1_12
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Algorithm to Find the Best Subsequence Patterns

Abstract: Given two sets of strings, consider the problem to find a subsequence that is common to one set but never appears in the other set. The problem is known to be NP-complete. We generalize the problem to an optimization problem, and give a practical algorithm to solve it exactly. Our algorithm uses pruning heuristic and subsequence automata, and can find the best subsequence. We show some preliminary experiments, that convinced us that the approach is quite promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…We declare that this work generalizes and outperforms the ones accomplished in [8,9], since it is capable of discovering more advanced and useful patterns. In fact, we show some experimental results that convince us of the accuracy of our algorithms as well as their fast performances.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…We declare that this work generalizes and outperforms the ones accomplished in [8,9], since it is capable of discovering more advanced and useful patterns. In fact, we show some experimental results that convince us of the accuracy of our algorithms as well as their fast performances.…”
Section: Introductionmentioning
confidence: 73%
“…Substring patterns are possibly the most basic patterns to be used for the separation of two sets S, T of strings. Hirao et al [8] stated that such best substrings can be found in linear time by constructing the suffix tree for S ∪ T [12,21,7]. They also considered subsequence patterns as rules for separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea of the enumeration is similar to previous works [2][3][4][5][6]8]. The main contrivance of this paper is in the method for calculating the lower bound of the RSS score for specific subspaces of the pattern space.…”
Section: Branch and Bound Strategymentioning
confidence: 92%
“…Another situation is when we are given two sets of strings, where one set (positive set) consists of sequences known to possess some biological characteristic, while the other (negative set) consists of sequences known not to posses these characteristics. The problem is to find a discriminating pattern, that is, a pattern which occurs in most strings of the positive set, but does not occur in most of the strings of the negative set [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%